2005
DOI: 10.1136/ard.2004.023838
|View full text |Cite
|
Sign up to set email alerts
|

Chronic non-bacterial osteomyelitis in children

Abstract: Background: Chronic recurrent multifocal osteomyelitis (CRMO) in children is a chronic non-suppurative inflammation involving multiple sites. Some children affected by chronic non-bacterial osteomyelitis (CNO) do not have multiple lesions or a recurrent course. Objective: To characterise the long term outcome of children with the full spectrum of CNO. Methods: 30 children diagnosed with CNO were followed up for a mean of 5.6 years and their disease assessed using a clinical score, multiple imaging, and a diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
207
2
31

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(248 citation statements)
references
References 42 publications
8
207
2
31
Order By: Relevance
“…In agreement with the literature, the clavicle was one of the most commonly affected bones (34% of patients) (25). With 60 bone lesions identified, the lower extremity was the most affected part of the skeleton, similar to the findings of previous studies (15,16,26). A previous study showed an association between CNO and different skin manifestations, such as palmoplantar pustulosis and acne, in up to 23% of children (24).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In agreement with the literature, the clavicle was one of the most commonly affected bones (34% of patients) (25). With 60 bone lesions identified, the lower extremity was the most affected part of the skeleton, similar to the findings of previous studies (15,16,26). A previous study showed an association between CNO and different skin manifestations, such as palmoplantar pustulosis and acne, in up to 23% of children (24).…”
Section: Discussionsupporting
confidence: 81%
“…In our study, 62% of patients with CNO achieved remission after monotherapy with NSAIDs, which is lower than the value reported in most earlier investigations (maximum 80%) (16,24). In contrast, some studies have reported that only 13% of patients achieved clinical remission using NSAIDs (28).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In 2005, the term CNO was coined to describe all of these disorders, and the current understanding is that non-infectious inflammatory bone disorders present a clinical spectrum within which CRMO is the most severe form (Girschick, Raab et al 2005). There have been further attempts to classify patients into defined groups (unifocal nonrecurrent, unifocal recurrent, multifocal nonrecurrent, multifocal recurrent) to establish diagnostic criteria and to find prognostic indicators, although such classification criteria have not been uniformly adapted (Beck, Morbach et al 2010).…”
mentioning
confidence: 99%